CHANGES IN SUBFOVEAL CHOROIDAL THICKNESS AFTER INTRAVITREAL DEXAMETHASONE IMPLANT THERAPY FOR DIABETIC MACULAR EDEMA. Issue 6 (June 2021) - Moon, Ka Young; Choi, Shin Young; Song, Ji Hun
Abstract : Purpose: To investigate changes in subfoveal choroidal thickness (SFCT) and their relationship with best-corrected visual acuity and optical coherence tomography parameters after intravitreal dexamethasone implant injection for diabetic macular edema. Methods: Eighty-one eyes treated with dexamethasone implant injection for diabetic macular edema were evaluated for best-corrected visual acuity, central macular thickness, SFCT, and optical coherence tomography parameters at baseline and Weeks 7 and 14. Results: The mean baseline SFCT significantly decreased at Weeks 7 ( P < 0.001) and 14 ( P < 0.001). At Week 7, each 1- µ m reduction in central macular thickness and five Early Treatment Diabetic Retinopathy Study letters (−0.1 logarithm of the minimal angle of resolution) improvement were associated with SFCT reductions of 0.09 ( P = 0.002) and 3.91 ( P = 0.044) µ m, respectively. At Week 14, each 1- µ m reduction in central macular thickness was associated with a 0.14- µ m reduction in SFCT ( P < 0.001). Eyes with good functional and anatomical responses exhibited significantly greater SFCT reductions. Subretinal fluid resulted in greater SFCT changes ( P = 0.039) and better best-corrected visual acuity ( P = 0.033) at Week 7. A continuous ellipsoid zone/interdigitation zone layer was associated with a smaller mean SFCT at Week 7 ( P = 0.002) and better best-corrected visual acuity at Weeks 7 and 14 (both, P < 0.001). Conclusion: Changes in SFCT after dexamethasone implant injection therapy for diabetic macular edema may predict anatomical and functional outcomes and correlate with optical coherence tomography features that are known as predictors of treatment response. Abstract : Supplemental Digital Content is Available in the Text.After intravitreal dexamethasone implant injection for diabetic macular edema, we observed a significant decrease in subfoveal choroidal thickness and major improvements in central macular thickness and visual acuity by Weeks 7 and 14. The Subfoveal choroidal thickness reduction was significantly correlated with central macular thickness reduction, morphological features on optical coherence tomography, and vision improvement.